PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PASSION PLASTICS DI KOTA BATAM - Ana Rio Fika; Lukmanul Hakim; Catur Fatchu Ukhriyawati (EQUILIBIRIA, 2016)
The study entitled "The Effect of Compensation, work motivation and Work Environment on Employee Performance PT. Passion Plastics in Batam "aims to determine whether the compensation, work motivation and work environment, either partially or simultaneously affect the performance of employees. To examine these issues, the questionnaire was distributed to 40 employees. Then the data were analyzed using SPSS version 21 o'clock analysis techniques.             The results of the study showed that partially compensate positive and significant effect on the performance of employees with regression coefficient 2.143 and significant level of 0.039. Further work motivation and no significant negative impact on employee performance seen that the value of the regression coefficient of -1.277 and a significant level of 0.210. Then the work environment are positive and significant impact on the performance of employees with regression coefficient 3.283 with a significant level of 0.002. Based on simultaneously (Test F) there is a significant effect and positive effect on employee performance with regression coefficient 6.071 and significant level of 0.002.